Heart rate response and lactate accumulation in junior handballers during ion trial match play - Gupta, S.; Goswami, A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Handball is a high intensity team game, mostly dependent on aerobic metabolism but interspersed by fast running, jumping, and throwing the ball that greatly tax anerobic metabolism. Heart rate response considered as the best indicator of cardiovascular stress whereas lactate accumulation may give an idea about the metabolic demand of the game. Methods: Thirteen junior (U18) Indian handballers were the participants of this study. VO2max, maximal heart rate (HRmax), and heart rate at lactate threshold (HRLT) were determined on treadmill by graded exercise protocol. HR was continuously recorded by telemetry at an interval of 5 s, throughout the match. Fingertip blood samples were collected at 15 min, 30 min, 45 min, and 60 min of the match. Data were collected from 4 selection trial matches. Each match was played in two halves (30 min x 2), separated by 10 min interval. Results: VO2max, HRmax, and HRLT of the handballers (n=13) are 51.6±3.9 ml/kg/min, 199.3±4.1 beats/min, and 172.3±7.4 beats/min respectively. Mean HR of BACK are significantly higher than PIVOT in both the halves of the matches. However, no significant difference was found between 1st and 2nd half of the matches. BACK spent nearly 20% of the total time of match play above the lactate threshold level, which is significantly higher than PIVOT (13.1%). Mean HR for each 5 min of play may vary widely from 149.1 to 169.8 beats/min during the game but such variation does not exist for every 15 min of play (159.1 to 163.5 beats/min). Blood lactate levels of BACK are higher than PIVOT at 30 min, 45 min, and 60 min, although only 45 min value is significantly higher. Peak HR (191.6±4.1 beats/min) of the subjects attained during match play was significantly less than their HRmax (172.3±7.4 beats/min). Discussion: Although intermittent and high-intensity in nature, handballers, in majority of the time, play in the low-intensity zone such as low-intensity running, walking or jogging (Povoas et al., 2012, Karcher and Buchheit, 2014). Longer sprints and distance covered by BACK, than PIVOT, is responsible for higher mean HR in BACK. This may also be responsible for higher lactate accumulation in BACK. Frequent sprints, jumps, and throw for defense and attack allow BACK to play more time above the HRLT intensity when compared to PIVOT. Probably, the total number of attacks by both the teams, sprints, slow movements, jumps and throws are fairly equal in each 15 min of play but vary widely for each 5 min of play. Cardiovascular stress in handball, not even occasionally, reaches its tolerance limit